Inovação no setor público: percepção de uso do Sistema Eletrônico de Informações (SEI) por servidores da Pró-Reitoria de Gestão de Pessoas da UFSCar - Tamegushi, Mirele Lie (2021)
Public sector innovation is an issue that needs further study, as this approach is more widespread in private organizations. With the historical changes brought about by technological transformations and, more recently, by the internet, new challenges have been introduced in the administration of public services in Brazil. The consequence of this process of changes has boosted the implementation of information systems in the Federal public sector, capable of increasing transparency, autonomy, agility and, at the same time, bringing public agencies and their users closer together. In addition to increasing the efficiency of processes at the organizational level, the Federal Government's concern also refers to compliance with the current regulations, including the Law on Access to Information, nº. 12.527/2011, which guarantees access and disclosure of information and, more recently Decree nº. 8.539/2015, which provides for the use of electronic means for carrying out the administrative process. Therefore, the objective of the research can be expressed as analyzing the perception of use of the Electronic Information System (SEI) by employees of the Pro-Rectory for People Management (ProGPe) at UFSCar during the implementation process at the unit, in the period of June from 2018 to July 2020. The research strategy followed the precepts of the qualitative method, outlined as a single case study and the data collection was based on participant observation, documentary research, bibliographic research and application of questionnaires with users of the system. It was identified in this study that the innovative action of implantation of the SEI can be considered an organizational innovation in a broad sense and specifically a process innovation in the public sector, in which it generated significant changes in the support related to information technology in comparison to the existing procedures previously. The application of the questionnaires in two groups of ProGPe, management servers and servers with no leadership, management or advisory duties, revealed a high degree of satisfaction in the infrastructure offered (computer and internet) during the implementation process and other benefits generated by the replacement of the process on paper for electronic media, such as increased productivity, agility and reduced material expenses. However, in relation to the platform, the servers agreed that the SEI still needs improvements and enhancement of the tools to meet the existing demand at the unit.